Development of Book Planner Self-Management Media to Improve Disciplinary Behavior of High School Students - Faridah, Firyal; Afiati, Evi; Rahmawati, Rahmawati (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Developing a Self-Management Book Planner: Creative Solutions to Improve High School Students' Discipline. This research was carried out to develop a self-management media book planner. The aim of this research is to describe the process of developing self-management book planner media in improving disciplinary behavior in high school students. Students who are not disciplined can disrupt the academic process at school, especially in the classroom. Which will impact on being hampered in achieving success in learning and their future. This research uses research and development methods using the ADDIE model (analysis, design, development, implementation and evaluation). The results of the product feasibility test in terms of media and materials, language and practitioners obtained an average result of 87%, including the appropriate category to be implemented for students. Furthermore, the overall results of the initial product test on students reached 88% with a score of 421 out of 480, including in the very feasible category.Keywords: Media, Book Planner, Self-Management, Discipline